Soft Power Versus Hard Power: International Political Strategies of Great Powers - Yusran, Yusran (International Journal of Demos (IJD), 2025)
Abstract This study aims to analyze the use of soft power and hard power strategies in international politics carried out by major countries, and to understand how these two approaches complement or compete with each other in achieving national interests. Using descriptive qualitative methods, this study examines case studies in the United States and China over the last decade. The results of this study indicate that the hard power and soft power strategies implemented by the United States and China have a significant impact on the dynamics of international politics, both in the form of competition for global influence, regional stability, and changes in the world economic order. The United States tends to use its military superiority to ensure deterrence and enforce interests through economic sanctions, while its soft power derived from popular culture and democratic values remains a strong attraction in many countries. In contrast, China focuses on economic diplomacy through massive investment and strengthening trade relations that increase the dependence of its partners, accompanied by the modernization of its military as a guarantee of protecting strategic interests. The combination of the strategies of the two countries not only triggers competition in promoting development and governance models, but also creates a more complex international landscape, where narratives and public perceptions become new fields of competition besides the power of weapons and economy. Keywords: Soft Power, Hard Power, Smart Power, International Politics, United States, China